The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/cancers14082030
|View full text |Cite
|
Sign up to set email alerts
|

Proline Metabolism in Malignant Gliomas: A Systematic Literature Review

Abstract: Background: Proline has attracted growing interest because of its diverse influence on tumor metabolism and the discovery of the regulatory mechanisms that appear to be involved. In contrast to general oncology, data on proline metabolism in central nervous system malignancies are limited. Materials and Methods: We performed a systematic literature review of the MEDLINE and EMBASE databases according to PRISMA guidelines, searching for articles concerning proline metabolism in malignant glial tumors. From 815 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…Next, we assessed the mRNA levels of enzymes of the urea cycle and proline metabolism, since the polyamine precursor putrescine is synthesized from a non-proteinogenic amino acid ornithine of this cycle, which is also linked to Pro/Glu metabolic system [ 12 , 52 ]. The results, presented in Figure 5 a–c, show that in hepatocyte-like HepaRG cells, the level of the transcript encoding argininosuccinate synthase (ASS1) is fifteen-fold higher than in Huh7.5 cells, and the mRNA of the argininosuccinate lyase gene (ASL), which synthesizes arginine, is two times higher.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we assessed the mRNA levels of enzymes of the urea cycle and proline metabolism, since the polyamine precursor putrescine is synthesized from a non-proteinogenic amino acid ornithine of this cycle, which is also linked to Pro/Glu metabolic system [ 12 , 52 ]. The results, presented in Figure 5 a–c, show that in hepatocyte-like HepaRG cells, the level of the transcript encoding argininosuccinate synthase (ASS1) is fifteen-fold higher than in Huh7.5 cells, and the mRNA of the argininosuccinate lyase gene (ASL), which synthesizes arginine, is two times higher.…”
Section: Resultsmentioning
confidence: 99%
“…In Huh7.5 hepatoma cells, the expression of proteins synthesizing proline from P5C (PYCR1, PYCR2, PYCR3) prevails over proline-utilizing proteins (PRODH and PRODH2) and the coordinated action of PYCR3, PRODH, and PRODH2 proteins. P5C, being exported into the cytoplasm, is converted into proline, resulting in proline being transferred back to the mitochondria, where it was again oxidized into P5C by PRODH and PRODH2 [ 52 ]. Hence, a closed cycle leads to an increase in the concentration of NADP + in the cytoplasm and the generation of ROS in mitochondria [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current literatures found that the concentration of proline in GBM was higher than in normal brain 32 . Similarly, IDH-mutant high-grade oligodendrogliomas was found to utilize the proline cycle as a redox shuttle to maintain redox balance 33 . Our findings support the hypothesis that regulating the disorder of arginine and proline metabolism pathway in cancer cells can affect the proliferation of tumor cells, which provides a new idea for the targeted therapy of glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Proline is oxidized to glutamate in the mitochondria and has been linked to glutamate metabolism in GBM and cell proliferation (Cappelletti et al, 2018). In a recent systematic review, Sawicka et al found proline to be a prognostic factor and a signal of malignancy (Sawicka et al, 2022).…”
Section: Additional Metabolitesmentioning
confidence: 99%